The basic steps of analyzing the data outliers with mahalanobis distance (MDI) technique: a study on the influence of human capital investment at polytechnic in East Coast Malaysia - Farahiyah Akmal, Mat Nawi; Abdul Malek, A Tambi; Mazlina, Mamat (2019)
Data analysis involved the process of developing answers to research questions through the examination and clarification of data and data screening process is a crucial part to prepare the data for further analysis. Therefore, this paper will highlight on the steps of Mahalanobis distance (MDi) implementation as one of the techniques to remove the data outliers by using the Statistical Procedure of Social Science (SPSS) software. The paper is going to adopt the data derived from the study which was conducted in 9 polytechnic campuses in East Coast Malaysia- Kelantan, Pahang and Terengganu. The numbers of population (14=1408 respondents) are consists of the lecturers from various departments. While the sample size (n) are 345 respondents. The questionnaire was distributed to obtain the feedback from the respondents by using the stratified sampling procedure. The questionnaire was consisting of 8 section with 1 dependents variable, 6 independent variables and 1 moderator.